Possible evidence of excitonic condensation in a topological insulator - Ryo Mori; Kazuaki Takasan; Ping Ai; Samuel Ciocys; Kaishu Kawaguchi; Takeshi Kondo; Takahiro Morimoto; Alessandra Lanzara (Proceedings of the National Academy of Sciences, 2025)
The transient excitonic condensate is a nonequilibrium electron–hole Bardeen–Cooper–Schrieffer state in a photoexcited semiconductor and semimetal, where electron–hole pairs undergo a phase transition and condense into a single coherent quantum state. Despite numerous experimental works to realize the predicted excitonic condensation phase, experimental evidence still remains elusive. This is largely due to the absence of direct measurements of a material’s transient momentum-dependent electronic structure and the excitonic state in the condensation regime. Here, using time and angle-resolved photoemission spectroscopy, we find direct evidence of a transient excitonic condensate in the spin-polarized spatially indirect excitonic topological states in Bi 2 Te 3 . Accompanying the formation of the excitonic topological states by photoexcitation, we reveal a splitting of the hole’s and electron’s quasi-equilibrium chemical potential followed by the band flattening and backbending of the transient topological surface state. Moreover, within the same momentum range, we report a reshaping of the bulk valence band in the form of a Mexican-hat-like Bogoliubov dispersion—hallmarks of the excitonic condensation, followed by the opening of an energy gap at the Fermi level. The fluence and temperature dependence of these renormalization effects are reminiscent of excitonic condensation within Bardeen–Cooper–Schrieffer (BCS)-like behavior. These results, together with theoretical simulation, point to the possible formation of a transient excitonic condensate and provide opportunities to manipulate topologically protected Bose condensates with light.